Pengaruh Kepemimpinan, Lingkungan Kerja, Kepuasan Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Badan Pengawas Pemilihan Umum (BAWASLU) Lombok Barat - Ajeng Nuraulia; Surahman Hidayat (Kredibel: Jurnal Ilmiah Manajemen, 2026)
This research aims to determine the influence of leadership, work environment, job satisfaction and organizational culture on employee performance at BAWASLU LOBAR. This research is associative research with a quantitative approach. This research consists of four independent variables, namely leadership (X1), work environment (X2), job satisfaction (X3) and organizational culture (X4) as well as one dependent variable, namely employee performance (Y). The population in this study were 55 employees and sub-district supervisory committee (Panwaslu) of BAWASLU LOBAR. Data was obtained by distributing 55 questionnaires to employees and supervisory officers of Bawaslu Lobar. Data were analyzed with SPSS 23 using multiple linear regression. The results of this research indicate that leadership and organizational culture have a significant effect on employee performance. Meanwhile, the work environment and job satisfaction do not have a significant effect on employee performance. The results of this research show that leadership, work environment, job satisfaction and organizational culture can influence employee performance by 39.4%, while the remaining 60.6% of employee performance is influenced by other variables outside the regression model used in this research.